2012
DOI: 10.1038/nm.2692
|View full text |Cite
|
Sign up to set email alerts
|

MRSA epidemic linked to a quickly spreading colonization and virulence determinant

Abstract: The molecular processes underlying epidemic waves of methicillin-resistant Staphylococcus aureus (MRSA) are poorly understood1. While a major role has been attributed to the acquisition of virulence determinants by horizontal gene transfer2, there are insufficient epidemiological and functional data supporting that concept. We here report the spread of clones containing a previously extremely rare3,4 mobile genetic element-encoded gene, sasX. We demonstrate that sasX has a key role in MRSA colonization and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(233 citation statements)
references
References 29 publications
8
218
2
1
Order By: Relevance
“…Although all ST88 isolates tested in our study were MSSA isolates and were generally susceptible to antibiotics, the infections caused by these isolates should not be ignored. SasX was identified as a quickly spreading crucial determinant of MRSA pathogenic success in a recent study, which also showed that the frequency of the sasX gene among S. aureus and MRSA isolates in China increased from 19-31 % in 2003 to 21-39 % in 2011 (Li et al, 2012). Similarly, the prevalence of the sasX gene in S.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although all ST88 isolates tested in our study were MSSA isolates and were generally susceptible to antibiotics, the infections caused by these isolates should not be ignored. SasX was identified as a quickly spreading crucial determinant of MRSA pathogenic success in a recent study, which also showed that the frequency of the sasX gene among S. aureus and MRSA isolates in China increased from 19-31 % in 2003 to 21-39 % in 2011 (Li et al, 2012). Similarly, the prevalence of the sasX gene in S.…”
Section: Discussionmentioning
confidence: 91%
“…Adhesin genes (clfA, clfB, cna, fnbA, sdrC, sdrD and sdrE) and other virulence factor genes (icaA and arcA) were amplified according to the method of Campbell et al (2008). The Panton-Valentine leukocidin gene (pvl) and the MRSA-related sasX gene were amplified as described previously by Jarraud et al (2002) and Li et al (2012). Amplification of genes conferring resistance to mupirocin (mupA) and antiseptic (qacA/B) was carried out as described previously by Cadilla et al (2011) and Noguchi et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…S1C). Surface proteins IsdA and SasX are expressed by Chinese MRSA isolates (20). Incubation of affinity-purified IsdA 64-323 (P) or SasX precursor (P) with purified SrtA Ī”N24 and NH 2 -Gly 3 nucleophile resulted in sorting signal cleavage to yield the transpeptidation product (M), which could be blocked with the noncompetitive inhibitor N,N,N-trimethyl-2-(methylsulfonylthio)ethanaminium chloride (MTSET) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For MRSA, drug resistance is associated with therapeutic failure and increased mortality of human infections (31,32). Glycopeptide (vancomycin) resistance has transferred from enterococci to MRSA (33); the resulting VRSA strains are broadly antibiotic resistant and represent a global infectious threat (34,35). Daptomycin and linezolid have recently been licensed to address the threat of MRSA and VRSA infections (36,37).…”
Section: Selecting For S Aureus Variants With Increased Resistance Tmentioning
confidence: 99%